Pre-Wedding Counseling to Strenthen The Family - Mu’awanah, Elfi; Lating, Ainun Diana; Zuhdi, Muhammad Sholehudin; Hanifunashwa, Banin; Dzakiyatunnahwah, Alifah; Broto, Germino Wahyu; Yuanita, Yuanita (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
A soul mate cannot be summoned or chosen at will; when destiny brings two people together, no one can resist it. This study explores the process of marriage preparation and cultural traditions that accompany it, emphasizing the spiritual, psychological, and social dimensions of readiness for marriage. The participants in this research selected significant partners and engaged several family members and community figures to organize the wedding ceremony in accordance with local customs and Islamic values. Although not all traditional rituals were performed, the essential components were fulfilled to ensure a meaningful and complete marriage process. One of the key findings highlights the ritual of cleaning the groom’s house (house purification), which is rooted in the Islamic belief that “cleanliness is part of faith” (al-nadhafah min al-iman) and the value of ikram al-nafs wa al-duyuf (self-respect and hospitality). The study also examines the sequence of pre-wedding traditions, including sending messages to ancestors, organizing the wedding convoy (arak-arakan pengantin), attending the wedding feast (walīmat al-‘urs), and conducting ceremonies at both the groom’s and bride’s residences. These practices not only reflect adherence to local customs but also serve as symbolic expressions of faith, purity, and social unity. Ultimately, this study concludes that marriage, when carried out with awareness and preparation, becomes a path to achieving a relationship filled with peace (sakinah), affection (mawaddah), and mercy (rahmah).